Two Dimensional CFD Analysis and Flow Optimization of Transmission Cooling Scoop for Longitudinal Powertrain Applications - Jacob Viertel; Rachmadian Wulandana (Institute for Research on Innovation and Industrial System (IRIS), 2021)
Two dimensional finite area method simulation was conducted to optimize the convective cooling performance of a transmission cooling scoop for longitudinal vehicle powertrain applications. Cooling of the transmission in an automobile is important to prevent premature wear or sudden failure caused by prolonged overheating of internal transmission components. The most common method for transmission cooling requires a small energy input for powering a pump to cool the transmission by circulating transmission fluid through a heat exchanger. An alternative cooling method was designed utilizing a simple scoop geometry to induce forced convection from ambient air to cool the transmission with no energy input requirement. Two dimensional simulation of this alternative cooling method was conducted in ANSYS Fluent. Fluid flow and heat transfer performance were analyzed for three proposed cooling scoop designs. Further flow optimization was achieved with parametric study regarding angle at which the cooling scoop is positioned relative to the transmission. Three dimensional simulation was conducted for improved observation of the physical model. Based on the simulation results, optimal geometry and future design improvements have been determined. A peak simulated heat transfer of 11.14 kW/m^2 was achieved with scoop angle of 45 degrees. Future research investigating the effects of induced turbulence to improve convective heat transfer would be beneficial.